A new chemotype with high tricyclene content from the essential oil of Salvia aegyptiaca L. growing in Algerian Pre-Sahara. Issue 20 (13th October 2022) - Smaili, Tahar; Bendif, Hamdi; Zedam, Abdelghani; Flamini, Guido; Maggi, Filippo
Abstract: The essential oil obtained by hydrodistillation from the aerial parts of Salvia aegyptiaca L. (Lamiaceae) growing wild in pre-Saharan region of Algeria, was analysed by GC-MS. Forty-one compounds were detected, representing 87.9% of the whole oil. The essential oil of S. aegyptiaca is characterized by the predominance of monoterpene derivatives (70.6%). The major constituents were tricyclene (22.9%), followed by limonene (17.5%), β-pinene (7.4%), caryophyllene oxide (3.2%) and β-caryophyllene (3.1%). Tricyclene, the main component in our analysis is generally absent in the volatile oils from other Salvia species, therefore, the Algerian accession of S. aegyptiaca may be categorized as a new chemo-type.